Social network structure modulates neural activities underlying group norm processing: evidence from event-related potentials - Han, Mengfei; Han, Ruoxuan; Liu, Xin; Xie, Duo; Lin, Rong; Hao, Yaokun; Ge, Hanxiao; Hu, Yiwen; Zhu, Yuyang; Yang, Liu (Frontiers in Human Neuroscience, 2024)
IntroductionSocial ties play a crucial role in determining the health and wellbeing of individuals. However, it remains unclear whether the capacity to process social information distinguishes well-connected individuals from their less-connected peers. This study explored how an individual’s social network structure influences the dynamic processing of group norms, utilizing event-related potentials (ERPs).MethodsThe study involved 43 university students from the same class who participated in a social network study measuring metrics such as real-life social network size, in-degree, out-degree, and betweenness centrality. Subsequently, 27 students participated in an EEG study assessing their willingness to engage in various exercises after being exposed to peer feedback or in its absence.ResultsThe results indicate that an individual’s social network structure is significantly associated with the dynamic processing of group norms. Notably, well-connected individuals exhibited larger ERP amplitudes linked to feedback (e.g., N200, P300, and LPP), greater functional segregation within the brain network (e.g., local efficiency and clustering coefficient), and enhanced synchronization within frontal area and across different brain areas.DiscussionThese findings highlight that well-connected individuals possess enhanced sensitivity and efficiency in processing social information, pointing to potential areas for further research on the factors influencing social network evolution.